Production of energetic protons, deuterons, and neutrons up to 60 MeV via disruption of a current-carrying plasma column at 3 MA. (16th October 2020) - Klir, D; Shishlov, A V; Kokshenev, V A; Jackson, S L; Rezac, K; Cherdizov, R K; Cikhardt, J; Dudkin, G N; Fursov, F I; Krasa, J; Kravarik, J; Kubes, P; et al.
Abstract: Acceleration of ions to multi-MeV energies is investigated in various plasma devices to better understand processes in astrophysical plasmas and to develop efficient accelerators for a variety of applications. This paper reports the production of proton, deuteron, and electron beams in a z-pinch—a cylindrically symmetric plasma column that is compressed by its own magnetic field. For this work, the GIT-12 pulsed-power generator was used to drive a novel configuration of z-pinch that dramatically enhanced ion acceleration associated with disruption of the current by instabilities in the compressed plasma. During the disruption of 3 MA current, hydrogen ions were accelerated up to at least 50 MeV, which is almost a hundred-times the ion energy provided by the generator driving voltage of 0.6 MV. Under optimal conditions, the total numbers of hydrogen ions with energies above 20 and 50 MeV were 4 × 10 13 and 10 11, respectively. Accelerated deuterons produced one 20 ns (full width at half maximum) pulse of fast neutrons via D(d, n) 3 He and other nuclear reactions. A maximum neutron output of (1.0 ± 0.2) × 10 12 neutrons/sr was observed downstream, i.e., in the anode to cathode direction. In this direction, the maximum neutron energy reached 58 ± 7 MeV. Both ion and neutron beams in our experiment reached an end-point energy of about 60 MeV, which is the highest value observed in pulsed-power devices. A localized peak voltage of ≳60 MV was driven by the inductive energy that was stored around the plasma column and that was extracted during a sub-nanosecond current drop. Considering the natural occurrence of current-carrying columns in laboratory and space plasmas, the current interruption observed in z-pinches could represent a more general physical process that contributes to the efficient conversion of magnetic energy into the energy of particle beams in various plasmas.